Discretion in Professional Practice and in Engineering Ethics - Wajszczyk, Piotr (Annales. Etyka w Życiu Gospodarczym, 2015)
There is an ongoing investigation by scholars of ethics and economics into whetherhuman decision making and the resultant acts should be guided by rules and procedures or by judgment and discretion. Although each of these modes offers advantages and disadvantages to decision makers, they are by no means neutral intheir effect on professional development. The paper presents an in-depth view ofdiscretionary decisions using an Aristotelian-Thomistic framework.This is the first of the series of papers which focus on the application of realisticphilosophical principles to ethical professional behaviour and decision making indaily practice. Results indicate that classical philosophical theories which use virtues and truth as indispensable components still may give rise to desirable and moralconduct among individuals who apply them.